2020
DOI: 10.1002/pol.20190279
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Hyperbranched Polythioether Synthesis Through Thiol‐Michael Addition Reaction

Abstract: In this study, two types of hyperbranched (HB) polythioether could readily be achieved in a short time at ambient temperature through a thiol‐Michael addition reaction. Dimethyl acetylenedicarboxylate (DMADC) or methyl propiolate (A2) and trimethylolpropane tris(3‐mercaptopropionate) (B3) monomers were reacted using an organobase 1,5,7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD) as a catalyst in chloroform at room temperature to provide subsequent HB polythioethers. The effect of TBD concentration on the polymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…[ 6,15‐18 ] On the other hand, sulfur‐containing polymers including polythioethers, [ 19‐20 ] polythioesters, [ 21‐22 ] poly(monothiocarbonate)s, [ 23 ] polytrithiocarbonates, [ 24 ] polythioureas, [ 25 ] polythioamides, [ 26 ] polythiophenes, [ 27 ] and others, which generally enjoy high refractive indices, [ 28 ] excellent metal coordination ability, [ 25,29‐30 ] self‐repairing performance, [ 31 ] electrical conductivity, [ 27,32‐33 ] and degradability, [ 34‐36 ] have attracted much attention as advanced materials in the applications including optical materials, [ 37 ] sewage treatment materials, [ 30,38 ] self‐healing materials [ 31 ] and dielectric materials. [ 32,33 ] However, limited examples about sulfur‐containing hyperbranched polymers such as disulfide‐containing hyperbranched poly(amido amine)s with controllable bioreducibility and stimuli‐responsive property were developed, [ 39‐44 ] due to the lack of efficient synthetic approaches, and current methods generally involve sulfur‐bearing smelly and toxic monomers or byproducts.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 6,15‐18 ] On the other hand, sulfur‐containing polymers including polythioethers, [ 19‐20 ] polythioesters, [ 21‐22 ] poly(monothiocarbonate)s, [ 23 ] polytrithiocarbonates, [ 24 ] polythioureas, [ 25 ] polythioamides, [ 26 ] polythiophenes, [ 27 ] and others, which generally enjoy high refractive indices, [ 28 ] excellent metal coordination ability, [ 25,29‐30 ] self‐repairing performance, [ 31 ] electrical conductivity, [ 27,32‐33 ] and degradability, [ 34‐36 ] have attracted much attention as advanced materials in the applications including optical materials, [ 37 ] sewage treatment materials, [ 30,38 ] self‐healing materials [ 31 ] and dielectric materials. [ 32,33 ] However, limited examples about sulfur‐containing hyperbranched polymers such as disulfide‐containing hyperbranched poly(amido amine)s with controllable bioreducibility and stimuli‐responsive property were developed, [ 39‐44 ] due to the lack of efficient synthetic approaches, and current methods generally involve sulfur‐bearing smelly and toxic monomers or byproducts.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…0]dec‐5‐ene (TBD). [ 76‐78 ] A series of polythioethers (PTEs) with high M w values (up to 47400) were obtained in high yields (up to 99%) just for 1 min. Furthermore, different activated alkynes were adopted to polymerize with 1,6‐hexanedithiol, and the results demonstrated that dialkylacetylenedicarboxylates (DAADs) were much more active than alkyl propiolates ( M w up to 8900, yield up to 91%) and methyl phenylpropiolates ( M w up to 1200).…”
Section: Polymerization Of Di‐activated Internal Alkynesmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28] On the other hand, it has been proven that electron-deficient alkyne compounds are also suitable Michael acceptors to react with thiols and amines, and Michael addition reactions of these compounds with thiols and amines have gained much interest in polymer science since the last decade. [29][30][31][32][33][34][35][36][37][38][39] Notably, unlike the double bond analogues mentioned above, the electron-deficient alkyne compounds react more rapidly with thiols and amines, resulting in the formation of polymers and polymeric materials in short durations. 29,30 In this regard, in 2016, our group performed a series of condensation polymerizations between acetylenedicarboxylic acid and a variety of diols to prepare various polyesters containing electron-deficient alkyne units in the main chain.…”
Section: Introductionmentioning
confidence: 99%